KEBIJAKAN PEMERINTAH KOTA SEMARANG DALAM MEWUJUDKAN KOTA RAMAH LANSIA - Arneta Rahma Aqila; Hartuti Purnaweni; Budi Puspo Priyadi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
It cannot be denied that as time goes by, technology is increasing and ultimately affecting progress in various fields, one of which is the health sector. Improving the quality of health has an impact on increasing the number of elderly people in Indonesia, one of which is in Semarang City, the city with the largest population in Central Java. Elderly Friendly Cities are a solution to provide a better life for the elderly to live their lives. The purpose of this study is to describe and analyze the development of Semarang City government policies in realizing an Elderly Friendly City. To answer the problems and objectives of this study, the four conditions for an Elderly Friendly City according to WHO are used, combined with William Dunn's theory in analyzing the factors that influence the establishment of an Elderly Friendly City using a qualitative descriptive research method. In collecting data through interviews, documentation, and literature related to the title taken. The selected informants included: Bappeda, Social Service, Health Office, Central Java BKKBN, Population Control and Family Planning Office, and the elderly in Semarang City. The results of the study show that the realization of an Elderly Friendly City in Semarang City is not fully optimal. It is suggested that there is a big commitment from each executor to support the realization of an Elderly Friendly City both in providing a budget, providing local regulations, to awareness to create an Elderly Friendly City. It takes good communication coordination to support success